The Impact of Laboratory Management Module on Students' 4C Competencies in Physics Education - Laili, Ummiy Fauziyah; Yulianti Yusal; Munifah; Slez Nazy; Dalila Haji Daud (Universitas Muhammadiyah Makassar, 2025)
In today’s rapidly changing world, higher education is expected to equip students with the essential skills to thrive in global competition. Among these, the four core (4C) competencies—critical thinking, creativity, communication, and collaboration — are considered fundamental for success. Science laboratories hold great potential to cultivate these skills by providing students with direct, hands-on learning experiences. Yet, the benefits are often limited when laboratory activities are not supported by effective management. To respond to this challenge, this study explored how a laboratory management module influences students’ 4C skills. Using a quantitative survey design, data were collected from 142 undergraduates drawn from a total population of 208, with the sample size determined through the Isaac and Michael table. Two Likert-scale questionnaires measured students’ perceptions of the module and their mastery of the 4C skills. Data analysis employed Structural Equation Modeling with Partial Least Squares (SEM-PLS), enabling rigorous tests of validity, reliability, and causal relationships. The results indicate that the laboratory management module had a significant and positive impact on critical thinking and creativity, but no notable effect on communication and collaboration. This finding highlights the novelty of distinguishing between cognitive and interpersonal outcomes within laboratory management. The study concludes that structured laboratory management can serve as a powerful tool to enhance higher-order thinking, while additional strategies are needed to strengthen communication and teamwork. This study contributes to physics education by providing empirical evidence that structured laboratory management can effectively foster students’ critical and creative thinking skills. It also highlights the need to integrate collaborative and communication-focused strategies into laboratory practices.